Moderate to severe psoriasis patients' subjective future expectations regarding health‐related quality of life and longevity. (10th December 2014) - Rencz, F.; Holló, P.; Kárpáti, S.; Péntek, M.; Remenyik, É.; Szegedi, A.; Balogh, O.; Herédi, E.; Herszényi, K.; Jókai, H.; Brodszky, V.; Gulácsi, L.
Abstract Background Unrealistic expectations regarding treatments and clinical outcomes may lead to disappointment about therapy and sub‐optimal compliance; nonetheless, these expectations have not been studied in psoriasis patients yet. Objective To evaluate psoriasis patients' subjective future expectations regarding health‐related quality of life (HRQOL) and life expectancy, and to explore clinical features associated with under‐ or overestimating behaviour. Methods A cross‐sectional questionnaire survey of consecutive adult patients with moderate to severe psoriasis was conducted. HRQOL expectations were recorded by applying the EQ‐5D descriptive system for 6 months ahead and for future ages of 60, 70, 80 and 90 respectively. Results In total, 167 patients (71% males) were included in the analysis with mean age of 50.4 ± 12.4 years and mean EQ‐5D score of 0.71 ± 0.30. Overall 65% had chronic plaque psoriasis, 35% nail psoriasis, 35% scalp involvement, 29% psoriatic arthritis, 9% inverse psoriasis and 5% palmoplantar psoriasis respectively (combinations occurred). Participants expected 0.1 ± 0.23 mean improvement in EQ‐5D within 6 months (P < 0.001) that achieves the minimum clinically important difference. Overall 37% expected improvement and 13% decline; however, 49% expected no changes in any of the five dimensions of EQ‐5D within 6 months. Female gender, inverse or palmoplantar involvement and more severe psoriasis were likely associated with higher expectations. Patients at the initiation of their first biological at the time of the survey expected 0.18 ± 0.24 increase that seems to be realistic compared to the EQ‐5D utility gain achieved in randomized controlled trials. Males expected by 2.7 ± 11.1 more, while females expected by 5.2 ± 9.3 less life years compared to the average statistical gender‐ and age‐matched life expectancy (P < 0.05). Patients who expected to be alive at ages of 60, 70, 80 and 90 scored their future EQ‐5D at ages of 60 to 90: 0.59 ± 0.46, 0.48 ± 0.41, 0.42 ± 0.41 and 0.22 ± 0.47 respectively. Conclusion Our findings highlight the importance of exploring expectations that might help to increase patients' compliance.